Retroperitoneal Hematoma: What is the Procedure? - Barrón, Gema Méndez; Sánchez, Morelos Adolfo García; Cabello, José de Jesús Urbina; Valiente, Mariana González; Salvador, Judá Raquel Hernández; Acosta, Eduardo González; Marcial, Arturo Hernández; González, Estefanía Rojas; Daniel, Mayra Yadira Pérez; Rojas, Osvaldo Cristofer Rivas; Peña, Fiona Michelle Rosas; Castillo, Luis Fernando Flores (British Journal of Healthcare and Medical Research, 2025)
Introduction: the causes of retroperitoneal hematomas are multiple, acute and/or chronic; it is common for underreporting to be underreported, overtreatment or, worst of all, misdiagnosis. Objective: to present the surgical experience of the Surgery Service of the "Rubén Leñero" General Hospital of patients with retroperitoneal hematomas in Trauma Surgery in 5 years, in Mexico City. Method: retrospective, longitudinal, observational and descriptive study, in a period from 2020 to 2024, with a confirmed diagnosis of retroperitoneal hematoma. Results: 106 patients of which 94 (89 %) men, 12 women (11 %), mean of 27 years, 31 of them present with retroperitoneal hematoma. In this group of patients, 30 men (96.77%) and one woman (3.22%), with a mean age of 24 years, range from 18 to 33 years. The first cause of retroperitoneal hematoma is a blunt trauma of the abdomen due to a motorcycle accident, reaching 32.25%. Morbidity of 41.93% and zero mortality. Discussion: computed tomography is the gold standard for the diagnosis of retroperitoneal hematoma, with a sensitivity and specificity of 100%. The first organ affected retroperitoneally is the colon, in the second pancreas, and in the third place the kidney. Conclusion: the incidence of retroperitoneal hematoma is low when compared to anterior abdominal lesions with hemoperitoneum. Conservative management is the most appropriate approach, reducing morbidity and bleeding and avoiding overtreatment, with beneficial and correct results for patients.